2019
DOI: 10.1002/aoc.5294
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, biological screening and molecular docking of Zn(II) and Cu(II) complexes of 3,5‐dichlorosalicylaldehyde‐N4‐cyclohexylthiosemicarbazone

Abstract: A 3,5‐dichlorosalicylaldehyde‐N4‐cyclohexylthiosemicarbazone (C14H16Cl2N3OS) and its complexes [Zn(dsct)(phen)]·DMF (1), [Zn(dsct)(bipy)]·DMF (2), [Cu(dsct)(bipy)]·DMF (3) (phen = 1,10‐phenathroline, bipy = 2,2’bipyridine) were synthesized and characterized by CHN analysis, FT‐IR, UV–vis and NMR spectra. The molecular structure of the thiosemicarbazone (H2dsct) and its complexes have been resolved using single crystal XRD studies. In the complexes, thiosemicarbazone exist in the thioiminolate form and acts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…[ 96 ] On comparing the antibacterial activity of the Schiff base ligand (8.1 and 7.6 mm) with 3,5‐dichlorosalicylaldehyde‐ N 4 ‐cyclohexylthiosemicarbazone (0 and 4 mm), it can be seen that the prepared ligand exhibits more forceful activity against S. aureus and E. coli , respectively. [ 97 ] Also, comparing the antibacterial activity of compound 6 (14.6 and 13.9 mm) with [Cu(dsct)(bipy)]·DMF (0 and 8 mm), we found that the compound 6 is more efficient against S. aureus and E. coli . On comparing the zone of inhibitions of CuCl 2 compound 5 (14.8 mm) with [Cu(MnTSC) 2 ] (2.86 mm), the results show that former has better activity than the latter against the bacterial strain S. aureus .…”
Section: Resultsmentioning
confidence: 91%
“…[ 96 ] On comparing the antibacterial activity of the Schiff base ligand (8.1 and 7.6 mm) with 3,5‐dichlorosalicylaldehyde‐ N 4 ‐cyclohexylthiosemicarbazone (0 and 4 mm), it can be seen that the prepared ligand exhibits more forceful activity against S. aureus and E. coli , respectively. [ 97 ] Also, comparing the antibacterial activity of compound 6 (14.6 and 13.9 mm) with [Cu(dsct)(bipy)]·DMF (0 and 8 mm), we found that the compound 6 is more efficient against S. aureus and E. coli . On comparing the zone of inhibitions of CuCl 2 compound 5 (14.8 mm) with [Cu(MnTSC) 2 ] (2.86 mm), the results show that former has better activity than the latter against the bacterial strain S. aureus .…”
Section: Resultsmentioning
confidence: 91%
“…While some chemical compounds may be highly biologically active on their own, they may also be quite poisonous to the organism or have poor solubility. These compounds can be coordinated with transition metal ions, such Zn(II), to increase the therapeutic effect provided by the organic part and enhance the resultant molecules' bioavailability (Mathews, Begum and Kurup, 2020), (Bazhina, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial and anticancer activities of the prepared compounds were screened. [ 10 ] The mononuclear Co (II), Ni (II), and Cu (II) chelates of the ONS tridentate ligand 4‐(1,5‐dimethyl‐3‐oxo‐2‐phenyl‐2,3‐dihydro‐1 H ‐pyrazol‐4‐yl)‐1‐(3‐hydroxynaphthalen‐2‐yl)methylene)thiosemicarbazide were synthesized and characterized. The ligand coordinated to the metal center through azomethine nitrogen, phenolate oxygen, and thione/thiolate sulfur groups.…”
Section: Introductionmentioning
confidence: 99%